Human nature : nine ways to feel about our changing planet - Marvel, Kate (Ecco, an imprint of HarperCollins Publishers, 2025)
"Scientist Kate Marvel has seen the world end before, sometimes several times a day. In the computer models she uses to study climate change, it's easy to simulate rising temperatures, catastrophic outcomes, and bleak futures. But climate change isn't just happening inthose models. It's happening here... It's happening to us... Human Nature is [an] ... inquiry into our rapidly changing Earth. In each chapter, Marvel uses a different emotion to explore the science and stories behind climate change. As expected, there is anger, fear, and grief--but also wonder, hope, and love. With her singular voice, Marvel takes us on a soaring journey, one filled with mythology, physics, witchcraft, bad movies, volcanoes, Roman emperors, sequoia groves, and the many small miracles of nature we usually take for granted"--